The effect of educational intervention on sexual function of women referred to Health center of southern Tehran - Farahnaz Sabeti; Sedigheh Sadat-Tavafian; Fatemeh Zarei (Tehran University of Medical Sciences, 2018)
Introduction: Sexual health educationcan enable the people to improve their sexual behaviors. This study aimed to examine the impact of sexual education program on improving sexual behavior among  married women in Southern Tehran. Methods &Materials: This semi-experimental study was conducted on 130 women took part in two groups of  intervention and control (each one 65 individuals). The intervention group complied with two 180 -minute training sessions. Data were gathered from two groups at initial of the study and 3- month follow up through demographic questionnaire and scale of women sexual function and were analyzed with independent and paired T tests.  Findings: Totally 65 women took part with mean age of 35.6 ± 7.75 and 35.15± 6.85 in two groups of intervention and control respectively. At first, there were no significant differences between   two groups in terms of demographic characteristics and score of sexual function scale. However, after three months the sexual behaviors of intervention group (28.14 ± 3.44  were significantly much better than control group 22.79 ± 6.60  (p <0/0001). Conclusion: Sexual health training can improve sexual function in women. However sexual health training of women could be important approaches for improving the sexual function of women and  is recommended.